Smart Contracts and Blockchain Technology in Environmental Law for Sustainable Governance - Adnan Khaleel Kadhim; Mohammed Taqi Fadhil; Jasim Hameed Naseef; Nameer Hashim Qasim; Riyam M. Alsammarraie; Valeriian Shvets (Environment and Social Psychology, 2026)
This study examines how blockchain-based smart contracts can support environmental law enforcement by enhancing transparency, compliance monitoring, and regulatory coordination within legally pluralistic governance systems. despite the rapid expansion of blockchain applications in sustainability governance, existing research has largely examined smart contracts from technical or economic perspectives, with limited attention to their integration within formal environmental legal systems. this study addresses this gap by positioning blockchain-enabled smart contracts as legally embedded compliance-support instruments rather than purely technological solutions. A qualitative comparative case-study approach was employed, combining doctrinal environmental law analysis with examination of blockchain governance frameworks, statutory instruments, judicial rulings, and relevant policy documents. the study contributes novel empirical and conceptual insight by integrating sustainability-index modeling with legal analysis of smart contract–based environmental governance, a dimension insufficiently addressed in prior blockchain scholarship. a combination of stakeholder interviews and quantitative modeling also played key roles in assessing the effectiveness of integrated legal frameworks at reducing conflicts and driving sustainable outcomes. quantitative analysis was conducted using sustainability indices and governance-efficiency metrics derived from blockchain-based assessment models, enabling comparative evaluation of regulatory performance, compliance reliability, and cost-efficiency outcomes across jurisdictions. Findings indicate that regions implementing co-management agreements, along with culturally responsive policies, experienced marked declines in both, legal challenges and environmental harm. the percentage improvements reflect modeled regulatory-performance scenarios derived from comparative sustainability indices rather than experimental intervention outcomes. the sustainability indices were improved by 25-45% with cost-efficiency gains in the range of 18-25%. the findings further demonstrate that smart contracts, when embedded within existing statutory oversight mechanisms, can strengthen environmental enforcement through automated verification, immutable recordkeeping, and standardized sustainability reporting, without displacing judicial authority. stakeholder assessments indicated the highest acceptance levels when blockchain-supported regulatory frameworks aligned automated enforcement mechanisms with existing institutional and community governance structures. references to family and customary legal systems are incorporated only insofar as they affect the institutional implementation of environmental regulation and do not constitute the primary analytical focus of the study. the study emphasizes the necessity of adjusted, integrative legal frameworks that adhere to cultural standards, enhance legal institutions, and include local communities.